Villous tumor of the papilla of Vater Regarding a case treated by means of a cephalic pancreaticoduodenectomy - Estefan, Alberto; Grezzi, Roberto; Fernández, Gonzalo; Scigliano, Horacio (Cirugía del Uruguay, 1995)
The authors make a bibliographical revision as regards a case of villous tumor of Vater's papilla. They present the first case of villous tumor of the duodenum /oca/ized in Vater's papilla communicated in our country and treated by means of cephalic pancreatoduodenectomy with long term survival (3 years) and illustrate anatomopathological findings. They a/so revise these tumor's clinical presenta/ion, the values of diagnostic procedures and indications far curative treatment (endoscopica/ resection, duodenopapillectomy, segmentary duodenal resection and cephalic pancreatoduodenectomy) ar palliarive one (deriva/ion) according to Go/ondiuk's